2011
DOI: 10.1016/j.jaci.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity and bariatric surgery on airway hyperresponsiveness, asthma control, and inflammation

Abstract: Background Asthma in obese individuals is poorly understood, these patients are often refractory to standard therapy. Objectives To gain insights into the pathogenesis and treatment of asthma in obese individuals by determining how obesity and bariatric surgery affect asthma control, airway hyperresponsiveness and markers of asthmatic inflammation. Methods A prospective study of (i) asthmatic and non-asthmatic bariatric surgery patients compared at baseline, and (ii) asthmatic patients followed for 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
295
2
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(329 citation statements)
references
References 47 publications
11
295
2
13
Order By: Relevance
“…Macrophages play an important role in the pathogenesis of diseases related to the metabolic syndrome. Prior studies aimed at identifying possible mechanisms that mediate the overweight/obese asthma phenotype have determined that CD4 1 T cells do not appear to play a key role in this association (35). We now propose that alterations in macrophage responses create a unique inflammatory environment in the lungs of overweight/obese subjects with asthma.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Macrophages play an important role in the pathogenesis of diseases related to the metabolic syndrome. Prior studies aimed at identifying possible mechanisms that mediate the overweight/obese asthma phenotype have determined that CD4 1 T cells do not appear to play a key role in this association (35). We now propose that alterations in macrophage responses create a unique inflammatory environment in the lungs of overweight/obese subjects with asthma.…”
Section: Discussionmentioning
confidence: 76%
“…Lack of atopy may play a role in alterations in airway hyperresponsiveness in overweight/obese subjects with asthma (35); however, the underlying mechanisms are poorly understood. Our study was underpowered to detect any differences in macrophage responses based on the presence or absence of atopy.…”
Section: Discussionmentioning
confidence: 99%
“…Although asthma is usually associated with inflammation of the lungs, human studies have shown that obesity-related asthma is independent of airway inflammation (44)(45)(46). For example, Dixon and colleagues reported that weight loss by bariatric surgery reduces airway hyperresponsiveness in obese patients with asthma but does not decrease the proportion of lymphocytes in bronchoalveolar lavage fluid or T-cell production of inflammatory cytokines (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dixon and colleagues reported that weight loss by bariatric surgery reduces airway hyperresponsiveness in obese patients with asthma but does not decrease the proportion of lymphocytes in bronchoalveolar lavage fluid or T-cell production of inflammatory cytokines (46). Furthermore, sputum eosinophils are not higher in obese patients with asthma than in nonobese patients with asthma (7,45).…”
Section: Discussionmentioning
confidence: 99%
“…Even a moderate weight loss of 5–10% is sufficient to achieve clinical improvements [147]. Therefore, obese asthma patients are recommended to lose weight, possibly with the aid of a dietician.…”
Section: Management Of Severe Asthmamentioning
confidence: 99%